2016
DOI: 10.1111/bph.13427
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related differential effect of tachykinin NK2 receptor‐mediated visceral hyperalgesia in guinea pig colon

Abstract: BACKGROUND AND PURPOSE The tachykinin NK 2 receptor antagonist ibodutant is under Phase III clinical investigation to treat female patients with irritable bowel syndrome. The aim of this study was to investigate the NK 2 receptor-related gender specificity in a model of colitis. EXPERIMENTAL APPROACH Colitis was induced by rectal instillation of 2,4,6-trinitrobenzenesulfonic acid (TNBS, 0.5 mL, 30 mg·mL À1 in 30% ethanol) in female and male guinea pigs. Electromyographic recording of the responses to colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…NK2r antagonists have been proven effective in animal models of visceral hyperalgesia induced by inflammation [ 57 , 58 ] or WAS [ 59 ]. Nepadutant [ 58 ], ibodutant [ 57 ] or saredutant [ 59 ] were found able to inhibit rectal hypersensitive responses in rats, guinea-pigs or gerbils pretreated with Trinitrobenzenesulfonic acid (TNBS) or previously subjected to restraint, suggesting that the NK2r has a role in mediating visceral allodynia/hyperalgesia.…”
Section: The Enteric Neurotransmission As a Potential Target Of Ibmentioning
confidence: 99%
See 2 more Smart Citations
“…NK2r antagonists have been proven effective in animal models of visceral hyperalgesia induced by inflammation [ 57 , 58 ] or WAS [ 59 ]. Nepadutant [ 58 ], ibodutant [ 57 ] or saredutant [ 59 ] were found able to inhibit rectal hypersensitive responses in rats, guinea-pigs or gerbils pretreated with Trinitrobenzenesulfonic acid (TNBS) or previously subjected to restraint, suggesting that the NK2r has a role in mediating visceral allodynia/hyperalgesia.…”
Section: The Enteric Neurotransmission As a Potential Target Of Ibmentioning
confidence: 99%
“…NK2r antagonists have been proven effective in animal models of visceral hyperalgesia induced by inflammation [ 57 , 58 ] or WAS [ 59 ]. Nepadutant [ 58 ], ibodutant [ 57 ] or saredutant [ 59 ] were found able to inhibit rectal hypersensitive responses in rats, guinea-pigs or gerbils pretreated with Trinitrobenzenesulfonic acid (TNBS) or previously subjected to restraint, suggesting that the NK2r has a role in mediating visceral allodynia/hyperalgesia. This role was further supported by the studies of Birder et al [ 60 ], who showed that the increased expression of either c-fos and c-jun proto-oncogene markers in spinal cord and dorsal root ganglia neurons of rats pretreated with TNBS was prevented by nepadutant, and by Laird et al [ 61 ], who found nepadutant capable of preventing the hypersensitivity of single spinal cord neurons responding to colorectal distension or pelvic nerve stimulation in rats pretreated with intracolonic acetic acid.…”
Section: The Enteric Neurotransmission As a Potential Target Of Ibmentioning
confidence: 99%
See 1 more Smart Citation
“…Early study has shown that SP can be synthesized within the NG and bidirectionally transported toward the CNS and thoracic and abdominal viscera . Gender difference regarding SP released from primary afferents evoked by formalin has been reported recently . However, the resting level of SP in NG tissue and estrogen sensitivity have not been evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…29 Gender difference regarding SP released from primary afferents evoked by formalin has been reported recently. 30,31 However, the resting level of SP in NG tissue and estrogen sensitivity have not been evaluated. In this regard, ELISA assay was performed and the result showed no difference in serum level SP ( Figure S1) among adult male, age-matched female, and OVX female rats.…”
Section: Serum Level Of Substance Pmentioning
confidence: 99%